Factors Associated With Home Visit on Malaria Prevalence in Children under Age Five in Kibi in the East Akim Municipality of Ghana - Abilena, M.M. (University of Ghana, 2017)
Background: Home visit is a strategy used to reach out to members of a household for discussion and provision of health services by Community Health Officers. This approach is mostly used in deprived communities to provide health services at the doorstep of community members. Not much is known about this strategy in the public health sector. From the review of literature, malaria forms a significant proportion of diseases in most of the Out-Patient Departments. There are also a significant proportions of interventions which are ongoing to curb this trend in Kibi, therefore studying one of the components of the intervention is of much importance in advocating for the usefulness of home visit in a bid to prevent malaria in children under five years. Methodology: A cross sectional study design was used for the research. A stratified random sampling was also used in the selection of homes for the interview. The population of interest were children under five years. Total sample size of 300 was used for the study and a structured questionnaire was used to collect data from caregivers. Homes which were selected and not visited by Community Health Officers were selected for the study. Results: Absence of malaria as reported by caregivers for children under five was 50.7%. Proportion of homes visited by Community Health Officers was 35.8%. For homes that were visited 57 (19.0%) were visited once in a month while 82(27.3%) lasted for more than 30 minutes. Homes visited was significant in reporting absence of malaria in children under five. Fever was identified as the cardinal sign of malaria for most caregivers 195(65.0%) while bites of an infective female anopheles mosquito was identified by a majority (74.6%) of caregivers as the mode of malaria transmission. Most (60.3) children slept under an LLIN the previous night and this was significant in reporting absence of malaria in children. Majority of caregivers with malaria visited the hospital (77.1%) and 14.9% provided home based therapy for management of malaria. Conclusion: The research findings showed that homes visited by Community Health Officers had a significant association with reported absence of malaria. Therefore, for effective prevention of malaria, home visit should be encouraged while focusing on LLIN use for children under five years.
Thesis (MPH)
Keywords: Factors Associated; Malaria Prevalence; Children; East Akim; Kibi; Municipality